A Screening Design to Analyze the Influence of Technological Configurations on Techno-economic Parameters for Autonomous Distilleries in Brazil - E.C. Rivera; V.C. Geraldo; N. Sanghikian; T.L. Junqueira; D. Capitani; C.D.F. Jesus; R. Maciel Filho; A. Bonomi (Chemical Engineering Transactions, 2014)
This study aims to assess how Internal Rate of Return of the enterprise, Ethanol Output and Surplus Electricity vary according to changes in existing scenarios of an autonomous distillery, that is, a distillery producing ethanol and electricity, but not sugar. A simulation procedure using the Virtual Sugarcane Biorefinery (VSB) framework according to a screening design is used for this purpose. The VSB is composed of a set of computer-aided tools to simulate the sugarcane agricultural production system, its transport as well as the industrial processing. The sensitivity of operational variables, such as fermentation yield, steam consumption, boiler steam pressure, juice extraction yield, residual ethanol concentration in vinasse and alcohol content in wine were varied in a realistic basis, constrained by operational limits, which resulted in forty-five scenarios following a Central Composite Design (CCD). This design was used to describe ethanol production possible scenarios in autonomous distilleries in Brazil. This procedure has allowed evaluating scenarios with different technological configurations. The influence of these operational variables on the techno-economic parameters was studied through a screening procedure for statistical evaluation of results.